Flavonoid Biosynthesis Is Likely More Susceptible to Elevation and Tree Age Than Other Branch Pathways Involved in Phenylpropanoid Biosynthesis in Ginkgo Leaves - Zou, Kai; Liu, Xueduan; Zhang, Du; Yang, Qin; Fu, Shaodong; Meng, Delong; Chang, Wenqi; Li, Rui; Yin, Huaqun; Liang, Yili (Frontiers in Plant Science, 2019)
Ginkgo leaves are always resources for flavonoids pharmaceutical industry. However, the effect of the elevation and tree age changes on flavonoid biosynthesis have not been detailly explored in Ginkgo leaves. In addition, whether these environmental pressures have similar effects on the biosynthesis of other nonflavonoids polyphenolics in phenylpropanoid biosynthesis is not known at present. In this research, de novo transcriptome sequencing of Ginkgo leaves was performed coupled with ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry analyses to obtain a comprehensive understanding of the influence of elevation and tree age on phenylpropanoid biosynthesis. A total of 557,659,530 clean reads were assembled into 188,155 unigenes, of which 135,102 (71.80%) were successfully annotated in seven public databases. The putative DFRs, LARs and ANRs were significantly up-regulated with the increase of elevation in young Ginkgo tree leaves. The relative concentration of flavonoid derivatives with high parent ion intensity was likely to imply that the elevation increase promoted the biosynthesis of flavonoids. Complex gene variations involved in flavonoid biosynthesis were observed with the tree age increase. However, flavonoid derivatives analysis predicted that the rise of tree age was more likely to be detrimental to the flavonoids manufacture. Otherwise, multiple genes implicated in the synthesis of hydroxycinnamates, lignin, and lignan exhibited fluctuations with the elevation increase. Significantly up-regulated CADs and down-regulated PRDs potentially led to the accumulation of p-Coumaryl alcohol, one of the lignin monomers, and might inhibit further lignification. Overall, the putative DFRs seemed to show more considerable variability towards these stress, and appeared to be the main regulatory point in the flavonoid biosynthesis. Light enhancement caused by elevation increase may be the main reason for flavonoids accumulation. Flavonoid biosynthesis exhibited a greater degree of perturbation than that of hydroxycinnamates, lignins and lignans, potentially suggesting that flavonoid biosynthesis might be more susceptible than other branch pathways involved in phenylpropanoid biosynthesis. This research effectively expanded the functional genomic library and provide new insights into phenylpropanoid biosynthesis in Ginkgo.